The Developing Students' Creativity through the Traditional House Miniature Project Using Ice Cream Sticks in the Strengthening Pancasila Student Profile (P5) Project in Grade VI at SDN 97/IV, Jambi City - Ardi Nur Hanafi; Annisa Rahmawati Siregar; Aprilia Widiastuti; Lela Rahmawati; Maharani Putri Rahayu; Destrinelli; Muhammad Sofwan (The Future of Education Journal, 2024)
This study aims to develop students' creativity through a project of making traditional house miniatures from ice cream sticks as part of the Strengthening Pancasila Student Profile (P5) project in grade VI at SDN 97/IV, Jambi City. The research method used is qualitative with a phenomenological approach, involving observation, interviews, and documentation. The results of the study show that project-based learning is effective in enhancing students' creativity, measured through indicators such as curiosity, self-confidence, perseverance, and imagination. This project also supports the achievement of the Pancasila Student Profile elements, namely creativity, mutual cooperation, and global diversity. Students actively engage in designing and completing the traditional house miniatures by creatively overcoming resource limitations, while drawing inspiration from Indonesia's cultural diversity. Thus, this project not only enhances creative thinking skills but also strengthens students' character in line with the goals of 21st-century education.